Medical and genetic correlates of long-term buprenorphine treatment in the electronic health records - Maria Niarchou; Sandra Sanchez-Roige; India A. Reddy; Thomas J. Reese; David Marcovitz; Lea K. Davis (Translational Psychiatry, 2024)
Abstract Despite the benefits associated with longer buprenorphine treatment duration (i.e., >180 days) (BTD) for opioid use disorder (OUD), retention remains poor. Research on the impact of co-occurring psychiatric issues on BTD has yielded mixed results. It is also unknown whether the genetic risk in the form of polygenic scores (PGS) for OUD and other comorbid conditions, including problematic alcohol use (PAU) are associated with BTD. We tested the association between somatic and psychiatric comorbidities and long BTD and determined whether PGS for OUD-related conditions was associated with BTD. The study included 6686 individuals with a buprenorphine prescription that lasted for less than 6 months (short-BTD) and 1282 individuals with a buprenorphine prescription that lasted for at least 6 months (long-BTD). Recorded diagnosis of substance addiction and disorders (Odds Ratio (95% CI) = 22.14 (21.88–22.41), P = 2.8 × 10−116), tobacco use disorder (OR (95% CI) = 23.4 (23.13–23.68), P = 4.5 × 10−111), and bipolar disorder (OR(95% CI) = 9.70 (9.48–9.92), P = 1.3 × 10−91), among others, were associated with longer BTD. The PGS of OUD and several OUD co-morbid conditions were associated with any buprenorphine prescription. A higher PGS for OUD (OR per SD increase in PGS (95%CI) = 1.43(1.16–1.77), P = 0.0009), loneliness (OR(95% CI) = 1.39(1.13–1.72), P = 0.002), problematic alcohol use (OR(95%CI) = 1.47(1.19–1.83), P = 0.0004), and externalizing disorders (OR(95%CI) = 1.52(1.23 to 1.89), P = 0.0001) was significantly associated with long-BTD. Associations between BTD and the PGS of depression, chronic pain, nicotine dependence, cannabis use disorder, and bipolar disorder did not survive correction for multiple testing. Longer BTD is associated with diagnoses of psychiatric and somatic conditions in the EHR, as is the genetic score for OUD, loneliness, problematic alcohol use, and externalizing disorders.